A Three‐Electrode, Battery‐Type Swagelok Cell for the Evaluation of Secondary Alkaline Batteries: The Case of the Ni–Zn Battery. Issue 4 (28th January 2016) - Garcia, Grecia; Schuhmann, Wolfgang; Ventosa, Edgar
Abstract: Three‐electrode cells are essential in understanding battery materials under operando conditions. A three‐electrode, battery‐type Swagelok cell for electrochemical studies of secondary alkaline batteries, in particular Ni–Zn batteries, is presented. The relevance of the three‐electrode battery‐type cell (i.e. sealed and non‐flooded) configuration is demonstrated as analytical tool with three observations: 1) The Ni electrode is shown to limit the system in the first cycles, while the Zn electrode becomes limiting in subsequent cycles. 2) Non‐woven separators (NWSs) clearly improve the performance of the battery. Besides the known fact of hindering the dendritic growth of Zn, NWSs inhibit the evolution of oxygen and hydrogen at the positive and negative electrodes. 3) The kinetics of the Ni electrode is much slower than that of the Zn electrode, as derived from the charge‐transfer resistance of the Ni electrode, which is substantially larger than that of the Zn electrode. Abstract : Three‐electrode cells are essential in understanding battery materials under operando conditions. A battery‐type Swagelok cell for alkaline batteries is presented as well as several examples of its importance for investigating Zn–Ni secondary batteries.